Imaging amide proton transfer and nuclear overhauser enhancement using chemical exchange rotation transfer (CERT). Issue 2 (2nd December 2013) - Zu, Zhongliang; Xu, Junzhong; Li, Hua; Chekmenev, Eduard Y.; Quarles, C. Chad; Does, Mark D.; Gore, John C.; Gochberg, Daniel F.
<x xml:space="preserve">Abstract</x> Purpose This study investigates amide proton transfer (APT) and nuclear overhauser enhancement (NOE) in phantoms and 9L tumors in rat brains at 9.4 Tesla, using a recently developed method that can isolate different contributions to exchange. Methods Chemical exchange rotation transfer (CERT) was used to quantify APT and NOEs through subtraction of signals acquired at two irradiation flip angles, but with the same average irradiation power. Results CERT separates and quantifies specific APT and NOE signals without contamination from other proton pools, and thus overcomes a key shortcoming of conventional CEST asymmetry approaches. CERT thus has increased specificity, though at the cost of decreased signal strength. In vivo experiments show that the APT effect acquired with CERT in 9L rat tumors (3.1%) is relatively greater than that in normal tissue (2.5%), which is consistent with previous CEST asymmetry analysis. The NOE effect centered at −1.6 ppm shows substantial image contrast within the tumor and between the tumor and the surrounding tissue, while the NOE effect centered at −3.5 ppm shows little contrast. Conclusion CERT provides an image contrast that is more specific to chemical exchange than conventional APT by means of asymmetric CEST Z‐spectra analysis. Magn Reson Med 72:471–476, 2014. © 2013 Wiley Periodicals, Inc.